Vetiver grass is capable of removing TNT from soil in the presence of urea - Das, Padmini K.; Datta, Rupali K.; Sarkar, Dibyendu; Makris, Konstantinos C. (My University, 2010)
The high affinity of vetiver grass for 2,4,6 trinitrotoluene (TNT) and the catalytic effectiveness of urea in enhancing plant uptake of TNT in hydroponic media we earlier demonstrated were further illustrated in this soil-pot-experiment. Complete removal of TNT in urea-treated soil was accomplished by vetiver at the low initial soil-TNT concentration (40 mg kg−1), masking the effect of urea. Doubling the initial TNT concentration (80 mg kg−1) significantly (p < 0.002) increased TNT removal by vetiver, in the presence of urea. Without vetiver grass, no significant (p = 0.475) change in the soil-TNT concentrations was observed over a period of 48 days, suggesting that natural attenuation of soil TNT could not explain the documented TNT disappearance from soil.
Keywords: 2,4,6-trinitrotoluene (TNT); Urea; Phytoremediation; Chaotropic effect; Bioremediation